2011
DOI: 10.1136/sextrans-2011-050108.112
|View full text |Cite
|
Sign up to set email alerts
|

P1-S2.55 High incidence of HIV and low HIV prevention coverage among men who have sex with men in Managua, Nicaragua

Abstract: Background High rates of HIV and sexually transmitted infections (STI) are found in men who have sex with men (MSM) in Nicaragua. This study investigated HIV, STI, and risk behaviours in MSM. Methods From 9/2009 to 2/2010, MSM 18 years or older who gave written informed consent and reported having anal sex with a man in the last year were recruited using respondent-driven sampling in Managua. The survey process included audio computer assisted survey instruments (ACASI) and face-to-face interviews followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Five studies from four records enrolled MSM from the community ( figure 3 , online supplementary table S4 ) in specific areas in Australia 2, 31 El Salvador 1, 32 Guatemala 1 and Honduras 3, 33 and Nicaragua 1, 34 (n=3012). The summary average prevalence in these studies was 3.2% (95% CI 2.1% to 5.1%, I 2 78.3%) with moderate between study heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies from four records enrolled MSM from the community ( figure 3 , online supplementary table S4 ) in specific areas in Australia 2, 31 El Salvador 1, 32 Guatemala 1 and Honduras 3, 33 and Nicaragua 1, 34 (n=3012). The summary average prevalence in these studies was 3.2% (95% CI 2.1% to 5.1%, I 2 78.3%) with moderate between study heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…We screened the titles and abstracts of 3,316 unique records published after 1991 and the full text of 833 studies (Figure S1 in online Appendix). A total of 63 records was included with participants who were; sampled at random from the general population [19][20][21][22][23][24] or using alternative community-based methods, [25][26][27][28][29] MSM and male-to-female transgendered, [30][31][32][33][34][35] FSW, [36][37][38][39][40] and pregnant women. [41][42][43][44] Of these, 37 studies included patients attending healthcare settings.…”
Section: Search Resultsmentioning
confidence: 99%
“…This change in the demographics of HIV infection is mostly attributed to various anatomical, histological, and social factors [ 22 ], as well as to sexual practices among various groups. A 2010 report in Nicaragua indicated that a large percentage of homosexual men also had sex with women [ 23 ]. Based on this report, the incidence of HIV infection among men who have sexual relationships with men is low, whereas that among heterosexuals is high [ 24 ].…”
Section: Discussionmentioning
confidence: 99%